Case Report: Accessible Digital Musical Instrument Can Be Used for Active Music Therapy in a Person With Severe Dementia and Worsening Behavioral and Psychological Symptoms: A Case Study Over a Year and a Half - Kondo, Eisuke; Tabei, Ken-ichi; Okuno, Ryuhei; Akazawa, Kenzo (Frontiers in Neurology, 2022)
Despite the fact that accessible digital musical instruments can take into account the level of cognitive demands, previous studies have been conducted with patients with mild cognitive impairment (MCI), and it is not known whether they can be used by people with moderate to severe dementia or dementia with worsening behavioral and psychological symptoms of dementia (BPSD). The participant was an 88-year-old woman with vascular dementia (VaD) (Mini-Mental State Examination [MMSE] and Neuropsychiatric Inventory [NPI] scores: 8 and 20, respectively). Music therapy (MT) was provided twice a week for 15 min, and MT sessions spanned over 18 months. For the MT, we used the cyber musical instrument with score (Cymis), an accessible digital musical instrument; it could be played using a touch panel and switches. The cognitive function of the participant declined further, with MMSE scores of 4 after 1 year and 0 after 1.5 years. BPSD peaked with the NPI score of 54 at 1 year and declined thereafter, although only apathy remained. Despite these changes, during MT, she was able to play the accessible digital musical instrument and focus on the performance. These results suggest that even patients with severe VaD can play an accessible digital instrument and continue active music therapy even if their BPSD progress with cognitive decline.